The Effect of Pregnancy Massage on Sleep Quality for Pregnant Women in the Third Trimester (HEALTH CARE: JURNAL KESEHATAN, 2026)
Sleep disturbances in pregnant women are often experienced during the second and third trimesters of pregnancy, occurring due to physiological and psychological adaptations. Sleep disturbances can lead to depression and stress, which may affect the fetus. Pregnancy massage can be one solution for women experiencing complaints of reduced sleep quality and back pain. The aim of this study is to determine the effect of pregnancy massage on changes in sleep quality in pregnant women in the third trimester in the service area of the Gunung Sari Health Center, Kampar District. The design used was a pre-experimental design in one group (one group pre-test post-test). The sample used consisted of pregnant women with a sampling technique using total sampling. The researchers administered treatment to the study group, which had previously undergone a pretest, and then conducted a posttest after the intervention. The pregnancy massage treatment was administered for 20 minutes, 4 times in 2 consecutive weeks. The quality of sleep of pregnant women was measured using the Pittsburgh Sleep Quality Index (PSQI). The data analysis used was the Wilcoxon test.  The results of the study showed that there was an effect of pregnancy massage on changes in the sleep quality of pregnant women in their third trimester in the working area of the Gunung Sari Community Health Center, Kampar Regency, with a p-value of 0.002 (p-value < 0.05). This clarifies that pregnancy massage has the potential to improve sleep quality, which affects the health of pregnant women.